Size effect of large high strength concrete beams with or without shear reinforcement - Fan, Shengxin (2023)
This paper presents a research programme conducted on a total of seven large high strength concrete (HSC) beams, up to 1800 mm in depth and 13400 mm in span, with and without shear reinforcement in the web. This study investigates experimentally the effects of aggregate size, shear reinforcement ratio, and effective depth on shear strength of large HSC beams. In addition, the test data are adopted for verification of design provisions in ACI 318–14, ACI 318–19 and EN 1992–1-1. It is experimentally shown that reduction in ultimate shear strength was observed with increasing beam depth, regardless of the maximum aggregate size and web reinforcement ratio. A larger beam depth led to a more extensive development of flexural and shear cracks, as well as a greater beam stiffness. Besides, the use of smaller aggregates results in a higher ultimate strength (in MPa) for the beams. Shear equations from ACI 318–14 overestimated shear strengths of the large HSC beams without web reinforcement, while ACI 318–19 and EN 1992–1-1 predictions were more conservative by accounting for the size effect term. It is also shown that the existing codes of practice could not account for the effect of aggregate size when determining shear strength. Additionally, predictions by all the three codes for the HSC beams with minimum shear reinforcement were generally conservative.